Bulletproof Monk - Hunter, Paul (Lakeshore Entertainment, 2003)
For 60 years, a mysterious monk with no name has traversed the globe to protect an ancient scroll, a scroll that holds the key to unlimited power. Now the Monk must look for a new scroll keeper. Kar is an unlikely candidate, a streetwise young man who only cares about himself. But when he inadvertently saves the Bulletproof Monk from capture, the two become partners in a scheme to save the world from the scroll's most avid pursuer. The Monk, Kar & a sexy Russian mob princess called Bad Girl must struggle to find, face and fight the ultimate enemy.